A indústria eletroeletrônica do Rio Grande do Sul : mapeamento da rota tecnológica, interação universidade-empresa, inovação e desenvolvimento econômico (1960-1990) - Bortolini, Edgar (2015)
This thesis presents the results of a historical research on the path of the companies in the electronics segment located in the state of Rio Grande do Sul in the period between the 1960s and 1990. The published studies on the subject follow two very clear lines: a) They are not written by historians, and therefore are more concerned with the presentation of the facts in chronological order "in the timeline" focused on the question "what was done" without interest in understanding "how" and "why" was made; b) are works that depict and design the trajectory of a particular company with a focus on its founder and relevant facts that could set an example for future generations, with no claim to look sideways interactions of that company with the other so as not point out the flaws that eventually (and almost always) occur in this trajectory. Thus, the proposal of this research follows the classical methodology of history, applying the technical and methodological knowledge of the Oral History aided by Textual Analysis Discourse in order to identify a set of key protagonists of the time and look through exclusive interviews, clarify what actually occurred, when it occurred and why. From several oral testimony and supporting research materials including government agencies research, it became clearer the path and especially the motivating factors that led these people to undertake a high-risk area, dominated by large multinational companies in a period of time characterized by great economic changes in Brazil. Finally, we recommend a few important points that can be followed by future researchers, and in subsequent follow-up investigations, which can enrich the research in this area.